Handbook of toxicology of chemical warfare agents - Gupta, Ramesh C. (Ramesh Chandra), 1949- (Academic Press, 2020)
Handbook of Toxicology of Chemical Warfare Agents, Third Edition, covers every aspect of deadly toxic chemicals used in conflicts, warfare and terrorism. Including findings from experimental as well as clinical studies, this essential reference offers in-depth coverage of individual toxicants, target organ toxicity, major incidents, toxic effects in humans, animals and wildlife, biosensors and biomarkers, on-site and laboratory analytical methods, decontamination and detoxification procedures, and countermeasures. Expanding on the second edition, Handbook of Toxicology of Chemical Warfare Agents has been completely updated, presenting the most recent advances in field. Brand new chapters include a new chapter on emergency preparedness, coverage of the chemical warfare agents used in Syria, the use of the Novichok agent in the UK, and more.